Impact of Educational Interventions on Knowledge About Hypertensive Disorders of Pregnancy Among Pregnant Women: A Systematic Review - Gholami, Kosar; Norouzkhani, Narges; Kargar, Meraj; Ghasemirad, Hamidreza; Ashtiani, Atieh Jafarabadi; Kiani, Shamim; Sajedi Far, Mahdi; Dianati, Maryam; Salimi, Yasaman; Khalaji, Amirmohammad; Honari, Sara; Deravi, Niloofar (Frontiers in Cardiovascular Medicine, 2022)
Background Hypertensive disorders of pregnancy (HDP), including chronic hypertension, preeclampsia and gestational hypertension, is the cause of about 50,000 deaths out of 400,000 perinatal deaths. HDP is an effective risk factor in stroke, type 2 diabetes, and cardiovascular diseases like ischemic heart disease. There is a significant relation between HDP, lifestyle, and knowledge. Unfortunately, many studies showed that pregnant women have lack of knowledge about HDP. Therefore, the importance of educational interventions is, today, more acknowledged than before. Aim The goal of this systematic review was to investigate the effect of interventional educations on the knowledge of pregnant women about HDP. Methods A systematic review of the related articles was conducted. We included English randomized controlled trials published up to December 2021, including pregnant women as population, HDP as the outcome, and educational interventions as the intervention. Results After the process of study selection, six articles containing 819 pregnant women were included in this study. Educational pamphlets, mobile-based application, a mixture of pamphlets, pictographic magnet and videos, and a combination of PowerPoint and data show projectors and conversation were the educational interventions in these studies. Conclusions The positive effects of educational interventions on the knowledge of women with HTP were observed in all studies. The higher knowledge leads to HDP-related complications. Systematic Review Registration https://archive.org/details/osf-registrations-gcs5r-v1, identifier: doi: 10.17605/OSF.IO/GCS5R.